A Critique of History, Religion and Social Issues in Nirad C. Chaudhuri’s The Continent of Circe - Dr. Boni D. Joshi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
Nirad Chaudhuri has been a celebrated social commentator on issues related to Indian history and social norms. A controversial figure for most of his life, he, in his unique sarcastic and scholarly manner holds a mirror to the contemporary society. Present research paper aims at tracing these debatable arguments made by him in select non-fiction works. Unlike writers of his age, he is not sympathetic about the conditions and miseries of Indian society but rather mockery and sarcasm are his favourite tools, of course, dipped in thorough researches available to him in his times. The thorough inclination for a pro-Anglican life style and detestation for Indian life can be observed in all of his works.